2015
DOI: 10.1186/s12953-015-0077-2
|View full text |Cite
|
Sign up to set email alerts
|

Proteome analysis of shell matrix proteins in the brachiopod Laqueus rubellus

Abstract: BackgroundThe calcitic brachipod shells contain proteins that play pivotal roles in shell formation and are important in understanding the evolution of biomineralization. Here, we performed a large-scale exploration of shell matrix proteins in the brachiopod Laqueus rubellus.ResultsA total of 40 proteins from the shell were identified. Apart from five proteins, i.e., ICP-1, MSP130, a cysteine protease, a superoxide dismutase, and actin, all other proteins identified had no homologues in public databases. Among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…The Hydractinia sequence was identified from a study of transcriptomes in feeding, reproductive and defensive polyps, and was expressed specifically in feeding polyps [62]. The Laqueus sequence was reported in a proteomic and transcriptomic study of the brachiopod shell matrix, and was identified specifically from the insoluble organic matrix [63]. These observations suggest that members of the Aquatic clade may play diverse biological roles.…”
Section: Discussionmentioning
confidence: 99%
“…The Hydractinia sequence was identified from a study of transcriptomes in feeding, reproductive and defensive polyps, and was expressed specifically in feeding polyps [62]. The Laqueus sequence was reported in a proteomic and transcriptomic study of the brachiopod shell matrix, and was identified specifically from the insoluble organic matrix [63]. These observations suggest that members of the Aquatic clade may play diverse biological roles.…”
Section: Discussionmentioning
confidence: 99%
“…We performed a shotgun approach to identify matrix proteins. The detailed procedures of tryptic peptide preparation and LC-MS/MS analysis are described in a previous study (Isowa et al. 2015).…”
Section: Methodsmentioning
confidence: 99%
“…We removed the low confidence PSMs and used the list of retained PSMs (FDR < 0.01) for the final protein identification. Parameters used for identification processes described earlier were the same as those in a previous study (Isowa et al. 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Proteomic studies suggest that, relative to other marine calcifiers, brachiopods precipitate their shells using a novel molecular mechanism. In the process, they might utilize an enzyme similar to that found in corals (αcarbonic anhydrase) to increase calcite precipitation rate (Jackson et al, 2015;Immel et al, 2015;Isowa et al, 2015). The secondary shell layer, most commonly used for reconstructions of paleoenvironmental conditions, is composed of calcite fibers that behave optically like single calcite crystals (Pérez-Huerta et al, 2018).…”
Section: Brachiopod Biomineralization and Potential Effects On δ 7 LImentioning
confidence: 99%